(untitled) (Annals of Medical Research, 2021)
Aim: We aimed to evaluate the frequency of paranasal pathologies and variations in migraine patients, and also whether such situations have an effect on the strength and frequency of pain attacks that the patients experienced. Materials and Methods: Patients between 18 and 58 years old were included in the study who were diagnosed as migraine according to International Classification of Headache Disorders (ICHD)-3 beta criteria. The images of patients whose axial and coronal brain CT examination were done are prospectively examined.Results: Totally 130 migraine patients were included in the study as 112 women (86.2%) and 18 men (13.8%). The average age of the patients was found as 32.5±10.4. Migraine with aura was observed in 31 of the cases (23.8%) and migraine without aura was observed in 99 (76.2%). It is found that the rate of paranasal pathology and / or variation in the patients with migraine as 76.9% in total. Conclusion: It is thought that paranasal regions should be evaluated carefully during the evaluation of brain imaging studies in terms of differential diagnosis of paranasal pathologies that may differ in treatment and prognosis in migraine patients. It is considered that there is a need for longitudinal and multi-centered studies regarding the matter. Keywords: Migraine; attack frequency; paranasal variation; paranasal pathology; pain severity.